From Plate to Planet: Redefining the Low-Carbon Tourism Experience and Investigating Its Influence on Gastronomy-Based Tourists’ Revisit Intentions and Environmentally Responsible Behaviours - Ekkarat Suwannakul; Siriporn Khetjenkarn; Inthawoot Suppavorasatit; Tansiphorn Na Nan (ABAC Journal, 2025)
Gastronomy tourism reflects key sustainability issues and has become an important means of supporting sustainable tourism. Many tourist cities have developed gastronomic and low-carbon travel activities to promote local food through tourism campaigns. However, the concept of low-carbon tourism (LCT) within the gastronomy context has not been explored adequately, and empirical research on the LCT experience from the demand side remains limited. This study employs mixed-methods research. First, the dimensions and attributes of the LCT experience of gastronomy-based tourists were developed and validated. Following the scale development process, a multidimensional LCT experience scale comprising seven dimensions was identified: learning, sensory, escapism, immersive, prestige, affective and sociocultural experience. Second, quantitative data collected from 947 participants were analyzed using structural equation modeling to examine the causal relationships between the LCT experience, experiential satisfaction, destination image, revisit intentions and environmentally responsible behavior among gastronomy-based tourists. The findings offer an extended view of the LCT experience from the perspective of gastronomy-based tourists and contribute to understanding how such experiences shape the tourists’ environmentally responsible behaviors and support sustainable tourism.
Keywords: Culinary Culture and Tourism; Diverse Aspects of Tourism Research; Environmental Sustainability in Business